Routledge handbook of south-south relations - Fiddian-Qasmiyeh, Elena 1978-; Daley, Patricia (Routledge International Handbooks, 2020)
South-South cooperation is becoming ever more important to states, policy-makers and academics. Many Northern states, international agencies and NGOs are promoting South-South partnerships as a means of ‘sharing the burden’ in funding and undertaking development, assistance and protection activities, often in response to increased political and financial pressures on their own aid budgets.